İslam borçlar hukukunda selem akdi - Kahya, Hatice Kübra (My University, 2012)
selem, akit, ma'dum, deyn ÖZET İSLAM BORÇLAR HUKUKUNDA SELEM AKDİ Selem akdi, akit esnasında özellikleri belirlenmiş madum bir malın, belli bir vadede temin edilip müşteriye teslim edilmek üzere, peşin bedel karşılığında satılmasını konu edinir. Akdin vade içermesi ve henüz tahsil edilmemiş şeyleri konu edinmesi, İslam hukukunda kredileşmeye imkan tanıyan model akitlerden biri olmasını mümkün kılar. Çalışmamızda, ma'dum'u konu edinmesiyle sisteme aykırı olarak nitelenen bu akdin mahiyeti incelenmiş, vadeli olup deyni konu edinmesinden dolayı, İslam'ın iki temel yasağı olan deyn'in deyn karşılığı satımı ve ribadan akdi koruma düşüncesi etrafında oluşturulan şartları incelenerek, diğer ivazlı akitler arasındaki yeri netleştirilmeye çalışılmıştır. Selem akdinin, cins borcunu konu edinmesiyle ivazlı akitlerin prototipi bey akdinden ayrıldığı temel noktalarına değinilerek, kabzdan önce tasarruf yasağı çerçevesinde, akdin konusuna ilişkin tasarruf biçimleri incelenmiştir. Ma'dumu konu edinmesiyle riskli bir işlem haline gelen bu akitte, îfâ esnasında, akdin konusu, teslim zamanı ve teslim yeriyle ilgili ortaya çıkabilecek problemler incelenmiştir. Son olarak selem akdi ile bey, istısna, karz, sarf, icare ve cuale gibi akitler mukayese edilerek, özellikle istısna, bey ve icare akitlerinin selem akdiyle olan organik bağlarına değinilmiştir. contract, salam, personal obligation

THE CONTRACT OF SALAM IN ISLAMIC LAW OF OBLIGATION Contract of salam consists of selling non-existent goods whose properties have been determined during the contract, in return for an advance price and by means of delivering to the buyer in a certain term. Contract of salam is one of the model contracts which makes credit supply possible, due to its including a certain term and also its having uncollected goods as a subject. In this thesis, I examined nature of salam contract which is described as an exceptional agreement because of its receiving the goods, which is not in the seller's possession at the time of the contract, as a subject. Besides, I analyzed the conditions of salam which have been composed with the thought of keeping the contract out of two essential prohibitions of Islamic law; “to buy deyn (personal obligation) in return for deyn” and “riba”. Thus, I tried to clarify salam’s position among other onerous contracts. I also handled the basic points of salam which differentiate it from simple sale, such as its being the prototype of onerous contracts on the grounds of its receiving obligation of defined type (cins borcu) as a subject. In addition, I studied on types of disposal on the subject of a contract, in the context of prohibition of disposal before receiving. I also investigated some probable problems –which arise from the risks of its receiving uncollected goods as a subject- about subject of contract, date and place of delivery. Lastly, I compared salam to other contracts like “bey, istisna, karz, sarf, icare and cuale”, spesifically explaining its organic relationship with “istısna, bey and icare”.
Keywords: Borçlar Hukuku; İslam Hukuku